Design of stimuli-responsive transition metal dichalcogenides - Ramon Torres-Cavanillas; Alicia Forment-Aliaga (Communications Chemistry)
Abstract Stimuli-responsive systems are an emerging class of materials in fields as diverse as electronics, optoelectronics, cancer detection, drug delivery, or sensing. Especially focusing on nanomaterials, 2D transition metal dichalcogenides have recently attracted the scientific community's attention due to their remarkable intrinsic stimuli-responsive behaviour upon external stimuli such as pH, light, voltage, or certain pathogens. This significant response can be further enhanced by forming mixed-dimensional heterostructures and by molecular functionalization, capitalizing on chemistry to manipulate and boost their intrinsic stimuli-responsive properties. Furthermore, thanks to the endless possibilities of chemistry, a new class of smart materials based on the combination of stimuli-responsive molecular systems with transition metal dichalcogenides has recently been synthesized. In these materials, the physical properties of the 2D layers are reversibly modified by the switchable molecules, not only enhancing their stimuli-responsive behaviour but also providing memory to the hybrid. Therefore, this review explores the recent breakthroughs in the chemical design of smart transition metal dichalcogenides with built-in responsiveness.